Accounting for inequality aversion can justify the 2° C goal - Marco Rogna; Carla J. Vogt (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
Impact assessment models are a tool largely used to investigate the benefit of reducing polluting emissions and limiting the anthropogenic mean temperature rise. However, they have been often criticised for suggesting low levels of abatement. Countries and regions, that are generally the actors in these models, are usually depicted as having standard concave utility functions in consumption. This, however, disregards a potentially important aspect of environmental negotiations, namely its distributive implications. The present paper tries to fill this gap assuming that countries egions have Fehr and Schmidt (1999) (F&S) utility functions, specifically tailored for including inequality aversion. Thereby, we propose a new method for the empirical estimation of the inequality aversion parameters by establishing a link between the well known concept of elasticity of marginal utility of consumption and the F&S utility functions, accounting for heterogeneity of countries/regions. By adopting the RICE model, we compare its standard results with the ones obtained introducing F&S utility functions, showing that, under optimal cooperation, the level of temperature rise is significantly lower in the last scenario. In particular, in the last year of the simulation, the optimal temperature rise is 2.1° C. Furthermore, it is shown that stable coalitions are easier to be achieved when F&S preferences are assumed, even if the advantageous inequality aversion parameter (altruism) is assumed to have a very low value. However, self-sustaining coalitions are far from reaching the environmental target of limiting the mean temperature rise below 2° C despite the adoption of F&S utility functions. – – Wir führen Ungleichheitsaversion im Sinne von Fehr und Schmidt (1999) in das RICE Modell von Nordhaus ein. Länder bzw. Regionen des Modells können durch Aversion gegen unvorteilhafte oder auch vorteilhafte Ungleichheit motiviert sein. Zur empirischen Abschätzung der Parameter der Fehr-Schmidt-Nutzenfunktion wird eine Beziehung zum empirisch gut untersuchten Konzept der Elastizität des Grenznutzens hergestellt. Es zeigt sich, dass die Aversion gegen unvorteilhafte Ungleichheit sich invers zum Pro-Kopf-Einkommen verhält, d.h. ärmere Akteure sind durch stärkere Grade der Aversion charakterisiert. Die Simulation des Modells ergibt einen optimalen Temperaturanstieg im Jahr 2100 von 2,1° Celsius im Vergleich zu 2,7° Celsius, die sich im Baseline unter der Annahme von Standardpräferenzen ergeben. Unsere Studie ist daher in der Lage, eine ökonomische Begründung für das Zwei-Grad Ziel des Paris Abkommens zu geben, auch wenn alle übrigen Bedingungen des Nordhaus-Modells, insbesondere die Diskontierungsrate sowie die Grenzschadensfunktion, konstant gehalten werden. Darüber hinaus zeigt sich im Optimalszenario eine weitaus stärkere Differenzierung der Vermeidungslasten: Reiche Länder müssen deutlich mehr vermeiden relativ zum Baseline-Modell, ärmere Länder deutlich weniger. Die Studie untersucht auch die Frage stabiler Koalitionen. Es zeigt sich, dass heterogene Ungleichheitsaversion zu signifikant mehr freiwilliger Kooperation im Klimaschutz führt. Allerdings kann auch im besten Fall eine Sieben-Länder-Koalition den Temperaturanstieg auf lediglich drei Grad begrenzen.
Keywords: C72; D63; Q54; 330; Abatement; climate policy; inequality aversion; Paris agreement; RICE model